TINJAUAN YURIDIS KEJAHATAN SKIMMER TERHADAP PEMBOBOLAN ANJUNGAN TUNAI MANDIRI (ATM) BANK DITINJAU MENURUT UNDANG-UNDANG NOMOR 10 TAHUN 1998 TENTANG PERBANKAN - Mandiri Mandiri (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTThe development of the technological results in the banking sector that can help facilitate the activities of banking transactions for customers is Automated Teller Machines (ATM) specifically to the ATM that became the focus of the author, in its development reap some threats and losses of the debiting of the ATM card which also serves as A Debit Card that reduces the number of accounts unwanted by the customer due to the actions and unlawful acts (PMH) of a third party by way of Skimming Card or the efforts of a person or a group of people to duplicate information contained in the magnetic tape on the ATM card. The prevention efforts contained in Law Number 10 of 1988 concerning Banking based on prudential principles as set forth in articles 29 and 47 on bank secrets and as well as prefentive action is the importance of providing legal protection for bank customers in the ATM use agreement by parties bank as an ATM card issuer that can minimize customer losses.